Power Dynamics in Minions: The Rise of Gru through Hobbes’s Leviathan - Suawah, Belinda Angela; Hidajat, Hayden Reinhart Christensen; Keitaro, Tan Farren; Gani, Sharren Rose; Habeahan, Noell Raja Pasaribu (Jurnal Pendidikan Makarios, 2026)
This study uses Hobbes’s Power Theory, The Social Contract Theory, from Leviathan (1651), as the main lens to analyze the movie, Minions: The Rise of Gru. Using a qualitative method of the research minions ac, the film's narrative, the research identifies three main Hobbesian parallels: 1) The Minions’ initial chaotic and ungoverned behavior perfectly represents the State of Nature, characterized by self-interest and disorder. 2) Gru's early actions, including his challenge to and theft from the Vicious 6, illustrate the inherent Hobbesian struggle for power and the conflict between individual ambition and existing authority. 3) Gru’s ultimate rise to leadership and the imposition of rules demonstrates the creation of the Leviathan (sovereign authority), which is necessary to curb chaos and unify the group with a shared purpose. The study concludes that the film supports Hobbes's central thesis: that strong authority and control are essential for transitioning from anarchy to a stable, purposeful society. It demonstrates that modern animation can serve as a literal case study for the Social Contract, where subjects trade total freedom for the protection of a "Sovereign." This research calls for further research by contrasting Hobbes’s "fear-based" authority with Machiavellian "virtue" to see how Gru maintains power.